Implementasi Problem Based Learning Berbantuan Google Sites pada Materi Pecahan: Studi Deskriptif Kualitatif - Wahyudi, Eko; El Walida, Sikky (JRPM (Jurnal Review Pembelajaran Matematika), 2026)
Fractions often present conceptual difficulties for students when instruction is dominated by procedural, teacher-centered approaches. This study aims to explain how Problem-Based Learning (PBL) assisted by Google Sites is implemented in fraction material and to explore students' responses and experiences during the process. This study used a descriptive qualitative design, with ten seventh-grade students at a Madrasah Tsanawiyah in Banyuwangi Regency selected as subjects through purposive sampling. Data were collected via classroom observations, semi-structured interviews with teachers and students, and documentation, then analyzed using the Miles and Huberman interactive model (data reduction, data display, and conclusion drawing). Data validity was established through technique and source triangulation. The results show that PBL assisted by Google Sites was implemented consistently according to PBL syntax, with Google Sites functioning effectively as a digital medium supporting independent and collaborative learning. Students generally showed positive responses and active engagement, though differences in ability and conceptual understanding remained challenges. Integrating PBL with simple digital media like Google Sites can support meaningful, student-centered fraction learning.